BODY IMAGE AMONG ADOLESCENTS WITH EATING DISORDERS - D. Ivanov; A. Khokhrina (Вестник университета)
The features of perception by adolescents of their own appearance as a factor favoring the emergence of eating disorders have been considered. The analysis of literature on psychological characteristics of people’s attitudes to themselves and their bodies has been made. It has been noted, that people’s attitudes to themselves and their bodies can cause eating disorders. The role of the media, which can provoke growing number of eating disorders, has been considered. The experiment, analysis of the research results of features of eating behavior among adolescents, dissatisfied with their own appearance, has been described. It has been shown, that adolescents, unsatisfied with their own appearance, often resort to restrictive and external eating behavior